To the question of determining the definitive component of the administrative and legal regulation of security activities - Kostyakov, Ihor (Actual problems of law (Aktual’ni problemi pravoznavstva), 2020)
The article explores the conceptual and categorical apparatus and analyzes such concepts as “regulation”, “social regulation”, “state regulation”, “legal regulation”, “administrative-legal regulation”, “legal impact”, “management” and “state control". The author’s vision of the category of administrative and legal regulation of security activities is proposed, which should be understood as the purposeful, normatively defined, authoritatively organizing influence of state-authorized entities (public authorities) on public relations arising from the implementation of security activities carried out using measures that are defined administrative law, with the aim of ensuring, first of all, the protection of the normal functioning of the state and society, and also the rights, freedoms and legal interferences of individuals and legal entities.